Alimentary tract duplications in children: report of 26 years' experience - Karnak, İbrahim; Öcal, Turgay; Şenocak, Mehmet Emin; Tanyel, F. Cahit; Büyükpamukçu, Nebil (The Turkish Journal of Pediatrics, 2000)
Duplications of the alimentary tract are one of the rare anomalies of the gastrointestinal system. Because of the wide spectrum of the signs and symptoms, preoperative diagnosis frequently cannot be made. A close familiarity with clinical and surgical characteristics provides appropriate management and treatment of duplications. A retrospective clinical study was conducted to evaluate clinical and surgical characteristics and the treatment of duplications of the alimentary tract.During a 26-year period between 1971 and 1997, 38 patients with duplications of alimentary tract underwent operation at the Hacettepe University Department of Pediatric Surgery. Forty-two duplications in 38 patients (20 male, 53%; 18 female, 47%) were encountered. Sixty-nine percent of the patients were symptomatic under the age of one year, with 24 percent presenting with symptoms in the neonatal period. There were one sublingual, nine intrathoracic (including 2 thoracoabdominal) and 32 intraabdominal duplications. Abdominal mass, abdominal distention, constipation, vomiting and respiratory distress were the most frequently encountered signs and symptoms. Plain thoracic and abdominal X-rays, ultrasonography, and computed tomography of the chest and abdomen were the most commonly used diagnostic radiological methods. Thirty-three duplications (79%) were spherical and nine (21%) were tubular. Multiple duplications were encountered in two patients (5.3%). Fourteen duplications (33%) contained heterotopic mucosa, mostly gastric type. More than one type of heterotopic mucosa in the same duplication was encountered in four duplications (10%). Additional malformations were encountered in 26 percent of patients. Six patients (15.8%) died from unrelated causes.The signs and symptoms vary among duplications. Signs and symptoms leading to diagnosis and surgery varied according to the age of patient, location of the duplication, type of mucosal lining, duration of disease and presence of complication. The ideal surgical treatment of duplication is complete excision. However, the other treatment options should be well known.
Keywords: alimentary tract; cyst; duplication; gastrointestinal; tubular